PENINGKATAN KEMAMPUAN INTERAKSI SOSIAL MELALUI PERMAINAN TRADISIONAL CUBLAK-CUBLAK SUWENG PADA ANAK AUTIS KELAS TIGA DI SLB - LESTARI, SRI (Jurnal Pendidikan Khusus, 2017)
Abstract: autisc children are children with development disorders. In a sense is a child who has a world of its own. Who have difficultyin social interaction. An traditional game cublak-cublak suweng spesially designed according to the conditions of students. The purpose of this study is to improve social interactionm skill in children with autism class III in SLB Harapan Bunda Surabaya. The method of thuis study using classroom action research (PTK) which learn took 2 cycles and each cycles was done 3 time meeting. The process of data collection is done by observation during the lening sesion. Result reseach on social interaction skills at a meeting average of 1,9. The first cycle with an average value 5,8 , the final cycle II with an average value 8. So the tradisional game cublak-cublak suweng can be used to improve social interaction skills student of class III SLB Autism Harapan Bunda.   Keywords: Traditional games, social interaction